The Influence of the Concept of Money and Monetary Policy in Islamic Economics - Moh Rizky Mulyadi; Moh Addul Gofar; Moh Aminulloh (Penerbit Hellow Pustaka, 2025)
Growth in the economy is an illustration of how implemented government policies affect the economy. Monetary development is the pace of development framed from different financial areas which by implication depicts the degree of monetary development that happens . Kuznets and Sirojuzilam define economic growth as